Weakly nucleophilic potassium aryltrifluoroborates in palladium-catalyzed Suzuki–Miyaura reactions: relative reactivity of K[4-RC6F4BF3] and the role of silver-assistance in acceleration of transmetallation - Bardin, Vadim V.; Shabalin, Anton Yu.; Adonin, Nicolay Yu. (Beilstein Journal of Organic Chemistry, 2015)
Small differences in the reactivity of weakly nucleophilic potassium aryltrifluoroborates are revealed in the silver-assisted Pd-catalyzed cross-coupling of K[4-RC6F4BF3] (R = H, Bu, MeO, EtO, PrO, iPrO, BuO, t-BuO, CH2=CHCH2O, PhCH2O, PhCH2CH2O, PhO, F, pyrazol-1-yl, pyrrol-1-yl, and indol-1-yl) with ArX (4-BrC6H4CH3, 4-IC6H4F and 3-IC6H4F). An assumed role of silver(I) compounds AgmY (Y = O, NO3, SO4, BF4, F) consists in polarization of the Pd–X bond in neutral complex ArPdLnX with the generation of the related transition state or formation of [ArPdLn][XAgmY] with a highly electrophilic cation and subsequent transmetallation with the weakly nucleophilic borate. Efficiency of AgmY as a polarizing agent decreases in order Ag2O > AgNO3 ≈ Ag2SO4 > Ag[BF4] > AgF. No clear correlation between the reactivity of K[4-RC6F4BF3] and substituent electron parameters, σI and σR°, of the aryl group 4-RC6F4 was found.
Keywords: potassium polyfluoroaryltrifluoroborate; silver(I) acceleration; Suzuki–Miyaura reaction